PHYLOGENETIC ANALYSIS OF RED COTTON BUG SPECIES (HEMIPTERA: PYRRHOCORIDAE) IN PUNJAB, PAKISTAN (Acta Entomologica Serbica, 2020)
Traditional techniques for identifying the red cotton bugs Dysdercus koenigii and Dysdercus cingulatus (Pyrrhocoridae: Hemiptera) depend on phenotypic and morphological data. These methods are suitable when species have well-defined structures and when huge taxonomic knowledge is at hand. In this study, the mitochondrial cytochrome oxidase I (COI) gene was selected for the molecular identification of D. koenigii and D. cingulatus. The sequence data showed that one species of the red cotton bug sample was identified as Dysdercus koenigii with 35-100% similarity to other Dysdercus species present in the NCBI database, while the other species was identified as Dysdercus cingulatus with 88-94% similarity to other red cotton bugs species present in the NCBI database. The phylogenetic analysis revealed that our D. koenigii Seq (>180319003-A02-102-DK-.ab1) shares the same cluster with four D. koenigii isolates (ZSI/SRC_I.28B, ZSI/SRC_I.28, GQ306227.1, KJ459924.1). While the D. cingulatus Seq (>180319003-A02-103-DC-.abl) shares a cluster with D. cingulatus voucher (RO_DC2015). This is the first molecular identification of red cotton bugs (D. koenigii and D. cingulatus) reported in Pakistan. Thus, in the current study, molecular identification has been accepted as a reliable method for the identification of these agriculturally important insect pests.